The asymptotics of constrained control in optimal singular parabolic problems - Kapustyan, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A complete asymptotic solution is constructed and justified for the optimal singular parabolic problems with constrained control and a completely degenerate differential part of an operator.